Isolasi Bakteri Fiksasi Nitrogen dan Fosfat pada Limbah Cair Karet (Hevea brasiliensis) - Sartika Kumala Dalimunthe; Kartika Manalu (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This research aims to determine which bacteria are capable of fixing nitrogen and dissolving phosphate in liquid rubber waste in Perdamean Village, Labuhanbatu Regency. The research method used was the description method with bacterial isolation techniques, then testing was carried out, namely the nitrogen fixation ability test and the phosphate solvent ability test. The results of the research showed that bacterial isolates capable of fixing nitrogen were found to have high absorbance values, namely 1,340 ABS. In the phosphate solubilizing ability test, there were 2 isolates that were unable to dissolve phosphate. In conclusion, isolating nitrogen and phosphate fixing bacteria in liquid rubber waste is a way to prevent pollution and destruction of the ecosystem in the environment. Keywords: Nitrogen Fixation, Rubber Liquid Waste, Phosphate Solvents